Fate and transport of paraquat dichloride in corn and rubber plantation soils - D. Keochan; W. Sinlapathorn; P. Phuinthiang; N. Nawinwattana; M. Jindakaraked; P. Kajitvichyanukul (Lowland Technology International, 2018)
The rubber and corn plantation soils in Nan province were investigated for the fate and transport behavior of the paraquat dichloride including biodegradation, adsorption, photolysis and infiltration. All experiments were conducted in the batch scale in laboratory basis. Results showed the biodegradation and photolysis were the main factors in decreasing the paraquat dichloride concentrations in the corn soil and rubber soil. The adsorption and infiltration described the holding and the leaching of paraquat dichloride of the soils. The biodegradation rates of paraquat dichloride in corn and rubber soils were 0.0548 and 0.0213 kg/day-mg, respectively. In photolysis reaction, the kinetic rate constants for corn and rubber soils were 0.017 and 0.0133 kg/min-mg, respectively. Corn and rubber soils had strong and quick adsorption for paraquat dichloride due to the soil textures of both two soils are clay and the high amount of cation exchange capacity. Corn soil had higher adsorption rate constant than rubber soil The adsorption behavior of paraquat dichloride in rubber soils is best described by Freundlich isotherm and that in the corn soil is best describe by Langmuir-II isotherm. The kinetic rate constants for photo-degradation of paraquat dichloride in corn and rubber soils were 0.0170 and 0.0133 kg/mg-min, respectively. From the mass balance, paraquat dichloride in leachates was detected in the lower amount than in the soil for both corn and rubber soils. Although paraquat dichloride can bound to organic matter or soil particles and adsorb in the soil, small amount of paraquat dichloride can be leached out to the groundwater.